2019
DOI: 10.3389/fonc.2019.00778
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Chemotherapy Response Score in Patients Affected by High Grade Serous Ovarian Carcinoma: The Prognostic Role of Omental and Ovarian Residual Disease

Abstract: Background: The chemotherapy response score (CRS) has emerged as a simple and reproducible histopathological grading system for assessing chemotherapy response in patients affected by ovarian high-grade serous carcinoma. Objective: To evaluate the prognostic impact of histological tumor response in ovarian and omental surgical specimens from patients with advanced stage ovarian high-grade serous carcinoma. Study Design: A cohort of 161 women were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 19 publications
(21 reference statements)
3
38
0
Order By: Relevance
“…Second, as information about BRCA 1/2 mutations was not available in most of the included patients, we could not conduct a more detailed subgroup analysis. Third, although the PFS of our cohort was in line with that of previous reports [16,18], the follow-up period in the present study was relatively short, and the median OS was not reached. Finally, the sample size of this work is limited.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Second, as information about BRCA 1/2 mutations was not available in most of the included patients, we could not conduct a more detailed subgroup analysis. Third, although the PFS of our cohort was in line with that of previous reports [16,18], the follow-up period in the present study was relatively short, and the median OS was not reached. Finally, the sample size of this work is limited.…”
Section: Discussionsupporting
confidence: 83%
“…In the 2019 European Society for Medical Oncology (ESMO) ovarian cancer guidelines, a three-tiered chemotherapy response score (CRS) system was recommended for patients receiving NACT to evaluate tumor response and predict prognosis [15]. Since its description, the CRS system has been independently assessed in many studies [16][17][18][19][20][21]. Currently, it is considered an accurate and highly reproducible method to predict survival outcomes for patients with tubo-ovarian high-grade serous carcinoma (HGSC) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The CRS system is the only method that is recommended in ESMO-ESGO guidelines for ovarian cancer patients to predict PFS and OS following NACT-IDS ( 3 ). Its reproducibility and accuracy have been validated in numerous studies ( 10 13 , 15 ). The omental response to NACT that was graded with the scoring system was reported to be even more important than debulking status for the prognosis of patients.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Böhm proposed a three-tiered chemotherapy response score (CRS) system based on the pathological examination of residual disease on omental specimens ( 9 ). Since its description, many studies have assessed the CRS independently and consistently validated it as a highly reproducible method to predict progression-free survival (PFS) and platinum sensitivity ( 10 15 ) for patients with tubo-ovarian high-grade serous carcinoma (HGSC). A recent meta-analysis by the HGSC CRS Collaborative Network confirmed that CRS 3 was significantly associated with improved OS ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in BET inhibitortreated mice, a significant decrease in PD-L1 expression was observed in macrophages isolated from ovarian tumor (17). Santoro et al indicated that the chemotherapy response score of neoadjuvant chemotherapy is a prognostic marker involving fibro-inflammatory change in TME (47). Furthermore, Grabosch et al demonstrated that neoadjuvant chemotherapy with cisplatin enhanced tumor immunogenicity and upregulated PD-L1 expression in ovarian cancer mouse models.…”
Section: Communication Between Macrophages and Tumor Cells Leads To Ementioning
confidence: 99%